AN ANALYSIS OF FLAVONOID COMPOUNDS FROM ETHANOL EXTRACT OF MORINGA LEAVES (MORINGA OLEIFERA L.) USING FTIR AND HPLC - Puruhita, Ranatri; Sulistyoningsih, Danik; Kristiyanti, Winnie; Aulia Rachma, Firstca (Science and Community Pharmacy Journal, 2024)
Moringa leaves contain flavonoids, phenols, tannins, alkaloids, saponins, terpenoids, and steroids. The flavonoid and phenol content has antioxidant activity. This research aimed to determine compounds in the ethanol extract of Moringa leaves To determine the type of flavonoid content using FTIR and HPLC. FTIR analysis shows that Moringa leaves possibly contain compounds from quercetin derivatives, which is supported by HPLC analysis. This quercetin compound is a group of flavonols that are characterized by the presence of a hydroxyl group and a carbonyl group. HPLC analysis was carried out by making a quercetin standard with a concentration of 200 ppm. The resulting wavelength is 254 nm. The results of the quercetin standard chromatogram which contains one main peak obtained from the quercetin standard. This peak shows the retention time at 3 minutes. The results of the standard chromatogram, quercetin has an outer area of ​​44763473 and a sample area of ​​17455781 with 2 times dilution, so the % purity of fraction 9 for quercetin is 77.99 ppm. This HPLC analysis shows that Moringa leaves probably contain quercetin derivatives which are characterized by the same retention time between the sample and the quercetin standard, namely at a retention time of 3 minutes, and have a peak pattern that is almost the same as the quercetin standard.